High‐precision isotopic analysis of essential mineral elements: capabilities as a diagnostic/prognostic tool. Issue 1 (5th November 2020) - Vanhaecke, Frank; Costas‐Rodríguez, Marta
Abstract: All elements with two or more isotopes show natural variation in their isotopic composition as a result of the isotope fractionation that accompanies (bio)chemical reactions and (bio)physical processes. Multicollector inductively coupled plasma‐mass spectrometry (MC‐ICP‐MS) offers the precision required to reveal and quantify the differences in isotope ratios thus caused, although they are often of sub‐permil magnitude only. Using MC‐ICP‐MS, it has been shown that (a) in different body compartments, essential mineral elements may display different isotopic compositions, and (b) disease conditions may alter the isotopic composition of an essential mineral element in a biofluid and/or tissue. As a result, high‐precision isotopic analysis of these elements is a powerful way to unravel the actual role these essential mineral elements play in specific biochemical processes. Moreover, isotope ratio shifts also show promise as a diagnostic or prognostic tool. Despite the intensive sample pretreatment preceding MC‐ICP‐MS isotopic analysis and the high purchase and running costs of the instrumentation, this approach may be valuable, especially for diseases that can otherwise only be established at a later stage and/or via a more invasive approach. This review paper describes the basics of "biomedical isotopic analysis" and uses selected cases from the literature to sketch the state‐of‐art and illustrate in which context isotope ratio markers could be exploited in a clinical context. Abstract : Disease conditions may alter the isotopic composition of an essential mineral element in a biofluid and/or tissue. Multicollector inductively coupled plasma‐mass spectrometry enables such changes in isotopic composition to be revealed and quantified. This approach is a novel way to unravel the actual role these essential mineral elements play in specific biochemical processes and shows promise for diagnostic and/or prognostic purposes. This review paper describes the basics of "biomedical isotopic analysis" and uses selected cases from the literature to illustrate how isotope ratio markers could be exploited in a clinical context.